Phenolic Compounds from The Stem Bark Erythrina Orientalis and Detection of Antimalaria Activity by ELISA - Tjitjik Srie Tjahjandarie (AIP Publishing, 2016)
Abstract. Erythrina orientalis has local name “Dadap”. This plant has known producing alkaloids, flavonoids, pterocarpans, stilbenes, and arylbenzofurans which are active compounds.Three prenylated flavonoids, 8prenyl-daidzein (1), alpinumisoflavone (2) and 4’-O-methyl licoflavanone (3) had been isolated from the stem bark of Erythrina Orientalis. The structures were elucidated on the basis of spectroscopic data,which ar IR, UV, MS, and NMR 1D ( 1 H-NMR and 13 C-NMR) and 2D (COSY, HMQC, and HMBC). Compounds 1-3 were evaluated for their antimalaria with ELISA methods, which showed percentage inhibitionvalues of74.46%, 62.06%, and 0% respectively. Based on the inhibition value showed 4’-O-methyl licoflavanone (1) exhibit very high antimalaria activity compared to compounds (2) and (3).